REVISITING THE ICONIC: THE EXCAVATION OF THE REELFITZ PIT ENGINE AND THE NEWCOMEN STEAM ENGINE IN CUMBERLAND, UK. (November 2014) - George, David; Nevell, Michael
Abstract : Examples of excavated 18th-century stationary steam engine sites are very rare in Britain. This article records the rescue excavations ahead of road-building works of one such site in 1974–5 at Reelfitz Pit in Little Clifton, Cumberland. The Reelfitz Pit pumping engine was built around 1780 and abandoned in 1781. The remains uncovered show that the site had two external boilers and a narrow engine house with a cylinder on the ground floor. The excavation uncovered three engine parts from within the engine house: the piston flange from the cylinder, the connecting link from the piston rod to the beam and one of the chain links which fitted into the piston head. The current work discusses the site in terms of the development of the West Cumberland coalfield and in the context of the surviving 18th-century Newcomen engines.